FAKTOR-FAKTOR YANG MEMPENGARUHI SIKAP KOMSUMEN RUMAT TANGGA DALAM MENGKONSUMSI CABAI MERAH (Capsicum annuum L.) DI KOTA PADANG - Ilham Martadona; Angelia Leovita; Tema Wahyuli (Universitas Galuh, 2023)
Red chili (Capsicum annuum L.) a commodity that is in great demand by almost everyone. Research objectives 1) to analyze the characteristics of red chili household consumers in Padang City; and 2) analyze the factors that influence the attitude of household consumers in consuming red chili in the city of Padang. The sampling technique was accidental sampling with a total of 44 people. Qualitative descriptive analysis method and quantitative analysis using multiple linear regression analysis. The results of the research on the characteristics of consumers consuming red chili in Padang City, are dominated by women (77.3 percent), with an age range of 24-29 years (38.6 percent), the highest education is SD/SMP/SMA (61.3 percent), married status (50.0 percent), with an income of 1,300,000 – 1,600,000 million (31.8 percent), with a total family member of 5 – 6 people (52.3 percent), has a spicy taste (59.1 percent) and with a purchase frequency of 1 x 3 days (72.7 percent). The results showed that the price variable and the education level variable were factors influencing the attitude of household consumers in consuming red chili.